PENGARUH PENGGUNAAN METODE QUANTUM READING TERHADAP MINAT BACA DALAM PEMBELAJARAN MEMBACA TEKS FABEL PADA SISWA KELAS VIII SMP NEGERI 10 MAKASSAR: THE EFFECT OF USING THE QUANTUM READING METHOD ON READING INTEREST IN LEARNING TO READ FABLE TEXTS IN CLASS VIII STUDENTS OF SMP NEGERI 10 MAKASSAR - Hasrawan, FItri; Usman; Nurhusna (Journal of Applied Linguistics and Literature, 2025)
This research is a quantitative study which aims to describe the influence of using the quantum reading method on reading interest in learning to read fable texts in class VIII students at SMP Negeri 10 Makassar. The research method used in this research is pre-experimental design with a One Group Pretest Posttest Design research design. Data collection techniques are in the form of tests which are divided into pretest and posttest. The population of this study were all students in class VIII of SMP Negeri 10 Makassar and samples were taken using a random sampling system technique. The samples taken were 32 (class VIII D) from a total of 165 students. Data analysis carried out in this research was descriptive statistics and inferential statistics.